Designing programs to improve diets for maternal and child health: Estimating costs and potential dietary impacts of nutrition-sensitive programs in Ethiopia, Nigeria, and India - Masters, William A.; Rosettie, Katherine L.; Kranz, Sarah; Danaei, Goodarz; Webb, Patrick; Mozaffarian, Dariush; Covic, Namukolo; Mavrotas, George (Oxford University Press, 2018)
Improving maternal and child nutrition in resource-poor settings requires effective use of limited resources, but priority-setting is constrained by limited information about program costs and impacts, especially for interventions designed to improve diet quality. This study utilized a mixed methods approach to identify, describe and estimate the potential costs and impacts on child dietary intake of 12 nutrition-sensitive programs in Ethiopia, Nigeria and India. These potential interventions included conditional livestock and cash transfers, media and education, complementary food processing and sales, household production and food pricing programs. Components and costs of each program were identified through a novel participatory process of expert regional consultation followed by validation and calibration from literature searches and comparison with actual budgets. Impacts on child diets were determined by estimating of the magnitude of economic mechanisms for dietary change, comprehensive reviews of evaluations and effectiveness for similar programs, and demographic data on each country.